UPAYA PENINGKATAN KESEHATAN IBU HAMIL DAN JANIN MELALUI EDUKASI NUTRISI SELAMA KEHAMILAN - Sambas, Etty Komariah; Syafariah, Yayah (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2024)
Fulfilling balanced nutritional needs and following nutritional standards during pregnancy has an important contribution to maintaining the health of the mother and fetus. Lack of nutritional intake during pregnancy can cause problems in the mother, such as anemia, premature birth pro, problems with fetal development, and the risk of fetal death. This community service activity aims to increase knowledge about nutrition during pregnancy. The activity method includes preparation in the form of coordination with health cadres and media preparation; implementation includes: reviewing the identity data of pregnant women, checking vital signs. height and weight measurements for basic data, as well as nutrition education during pregnancy.Educational media used audiovisual powerPoint and booklets. Educational methods are lectures, questions and answers, and interactive discussions. Educational evaluation in the form of pre and post-tests. The results of this activity showed that pregnant women were in the second and third trimesters, the results of examination of vital signs were in the normal range, body weight was appropriate for gestational age, and there was an increase in knowledge about nutrition during pregnancy with an average of 47%. Efforts to provide education to pregnant women need to be carried out continuously and comprehensively. This effort is necessary to ensure that pregnant women can maintain their health and that of the fetus they are carrying; this can be one of the factors that determine the outcome of safe/normal birth and health for the mother and baby.